Mapping the tumor microenvironment in clear cell renal carcinoma by single-cell transcriptome analysis - Wang, Yuxiong; Wang, Yishu; Liu, Bin; Gao, Xin; Li, Yunkuo; Li, Faping; Zhou, Honglan (Frontiers in Genetics, 2023)
While clinical outcomes remain unfavorable for patients with clear cell renal cell carcinoma (ccRCC), a comprehensive understanding of intratumoral heterogeneity holds the key to identify viable therapeutic targets for ccRCC treatment. Here, we conducted bioinformatic analysis to scrutinize the single-cell RNA sequencing data of seven ccRCC tumor and five para-tumor samples, with the primary aim of elucidating the intratumoral heterogeneity in the ccRCC tumor microenvironment (TME). A total of 51,780 single cells were identified and grouped into 11 cell lineages, including tumor cells, myeloid cells, T cells, fibroblasts, and endothelial cells, indicating the high heterogeneity of cell types in the TME. Moreover, our investigations revealed a predilection of the majority of immune cells in the TME toward adopting an inflammatory suppression state, thereby favoring the growth of tumor cells and enabling immune evasion. Copy number variation (CNV) analysis showed that the frequency of CNVs was higher in tumor cells than in normal cells. The myeloid cells were further re-clustered into three major subgroups: monocytes (cluster 4/7/9/10), macrophages (cluster 0/1/3/5/6/11), and dendritic cells (cluster 2/8/12/13). Differential expression analysis, gene ontology, and gene set enrichment analysis indicated both inter-cluster and intra-cluster functional heterogeneity within the ccRCC TME. Specifically, certain immune cells manifested pro-tumor and immunosuppressive effects, while others exhibited antitumor and immunostimulatory properties. Collectively, these results contribute to the understanding of the intratumoral heterogeneity in the ccRCC TME, and concurrently provide potential therapeutic targets for ccRCC treatment.